Fourth-order difference solvers for nonlinear delayed fractional sub-diffusion equations with variable coefficients. (2nd October 2017) - Xie, Jianqiang; Deng, Dingwen; Zheng, Huasheng
Abstract: In this paper, a compact difference scheme is established for nonlinear delayed fractional sub-diffusion equations. By the discrete energy method, it is shown that it achieves the convergence rate of in L ∞ - norm, and is unconditionally stable. Here, α is the order of fractional derivative. Besides, the extension of the solver to multi-term time fractional sub-diffusion equations with delays is discussed. Finally, numerical results demonstrate the effectiveness of our solvers.